Perkembangan Isu Sertifikasi Halal di Asia Tenggara - Tan Dwi Rizki Ramadini (Aksioreligia, 2025)
The halal food industry in Southeast Asia has experienced significant growth alongside the increasing Muslim population and rising global demand for halal products. In this context, halal certification has emerged as a strategic issue influencing consumer trust, industrial competitiveness, and regional market integration. This study aims to analyze the development of halal certification issues in the halal food industry in Southeast Asia, with particular attention to regulatory frameworks, cross-country differences in certification standards, and challenges faced by industry stakeholders. A qualitative literature review method was employed through a systematic examination of academic publications, government policy documents, and relevant industry reports. The findings indicate that government involvement, the role of national halal certification authorities, and efforts toward regional harmonization of halal standards are key factors supporting the growth of the halal food industry. Nevertheless, regulatory disparities, procedural complexity in certification processes, and limited awareness among business actors remain significant challenges. This study contributes conceptually to the literature on halal certification and provides insights for policymakers and industry practitioners in strengthening the halal food industry ecosystem in Southeast Asia.